Patient Reported Outcome (PRO) Among High-Grade Glioma Patients Receiving TTFields Treatment: A Two Center Observational Study - Onken, Julia; Goerling, Ute; Heinrich, Marcel; Pleissner, Stephanie; Krex, Dietmar; Vajkoczy, Peter; Misch, Martin (Frontiers in Neurology, 2019)
Introduction Patient reported outcome plays an increasingly important role in the evaluation of novel therapies for tumor patients. It has been shown that tumor treating fields (TTFields) in combination with standard therapy prolong survival in high-grade glioma (hgG) patients. But critics claim TTFields significantly impacts patients’ everyday life due to side effects and average daily time on therapy (18 hours) in a patient population with very limited life expectancy and high symptom burden. However, very limited data exist on patient reported outcome (PRO) for TTFields treatment. Methods This two center, observational study describes PRO of thirty hgG patients receiving TTFields in combination with chemotherapy. We introduced a device-specific questionnaire (DSQ) addressing device-specific restrictions and impact on daily live after 2 month of therapy. Additionally following questionnaires were used: EORTC (European Organization for Research and Treatment of Cancer) QLQ-30 (Quality of life of cancer patients), QLQ BN20 (Quality of life brain cancer module), QLQ FA13 (Cancer‐related fatigue), and SSUK-8 (social support). Results Surveys have been completed by 91% of enrolled patients. EORTC QLQ-30 revealed better physical, emotional and cognitive function than social and role function of study cohort. TTFields users reported frequently on positive social support and a low level of detrimental interactions. 71% of patients felt affected in daily life due to TTFields at least 2-3 times per week up to several times per day while maintaining high therapy compliance. Most frequent device-specific restrictions were duration of therapy (74%), size (66%) and weight (70%) of the device and changing time and bonding of the transducer arrays (66%, mean duration: 43.6 minutes). Restrictions on exercise of hobbies/work (63%/61%), body care (71%) and sexuality/relationship (64%) were most relevant. 70% would recommend TTFields to others and 67% would reuse TTFields treatment again based on their current experience. Conclusion The study shows that although TTFields treatment frequently affects everyday life in all aspects, therapy compliance was high and 67% of patients would reconsider TTFields for themselves. We propose that findings of PRO be taken into account for medical consultation about TTFields and in future device development to delivering high-value patient-centered care.